Commodity indexes for the Standard International Trade Classification (United Nations New YorkUS, 1994)
Volume 1 contains an item index which lists all basic headings of the SITC, Rev.3 in numerical order and provides for each basic heading an alphabetical list of representative commodities. Volume 2 contains an alphabetical index.
DC